Together Apart: The Mitigating Role of Digital Communication Technologies on Negative Affect During the COVID-19 Outbreak in Italy - Gabbiadini, Alessandro; Baldissarri, Cristina; Durante, Federica; Valtorta, Roberta Rosa; De Rosa, Maria; Gallucci, Marcello (Frontiers in Psychology, 2020)
The ongoing pandemic of COVID-19 has forced the governments to impose a lockdown, and many people have suddenly found themselves having to reduce their social relations drastically. Given the exceptional nature of similar situations, only a few studies have investigated the negative psychological effects of forced social isolation and how they can be mitigated in a real context. In the present study, we investigated whether the amount of digital communication technologies use for virtual meetings (i.e., voice and video calls, online board games and multiplayer video games, watching movies in party mode) during the lockdown promoted the perception of social support, which in itself mitigated the psychological effects of the lockdown in Italy. Data were collected in March 2020 (N = 465), during the lockdown imposed to reduce the COVID-19 spread. The results indicated that the amount of digital technologies use reduced feelings of loneliness, anger/irritability and boredom, and increased belongingness, via the perception of social support. The present study supported the positive role of digital technologies in maintaining meaningful social relationships even during an extreme situation such as a lockdown. Implications such as the need to reduce the digital divide and possible consequences of the ongoing pandemic are discussed.